Global water cycle and the coevolution of the Earth's interior and surface environment - Korenaga, Jun; Planavsky, Noah J.; Evans, David A. D. (Philosophical transactions of the Royal Society of London. Series A: Mathematical, physical, and engineering sciences, 2017)
The bulk Earth composition contains probably less than 0.3% of water, but this trace amount of water can affect the long-term evolution of the Earth in a number of different ways. The foremost issue is the occurrence of plate tectonics, which governs almost all aspects of the Earth system, and the presence of water could either promote or hinder the operation of plate tectonics, depending on where water resides. The global water cycle, which circulates surface water into the deep mantle and back to the surface again, could thus have played a critical role in the Earth's history. In this contribution, we first review the present-day water cycle and discuss its uncertainty as well as its secular variation. If the continental freeboard has been roughly constant since the Early Proterozoic, model results suggest long-term net water influx from the surface to the mantle, which is estimated to be 3−4.5×1014 g yr−1 on the billion years time scale. We survey geological and geochemical observations relevant to the emergence of continents above the sea level as well as the nature of Precambrian plate tectonics. The global water cycle is suggested to have been dominated by regassing, and its implications for geochemical cycles and atmospheric evolution are also discussed. This article is part of the themed issue ‘The origin, history and role of water in the evolution of the inner Solar System’.